Global surveillance for chemical incidents of international public health concern - B Olowokure; S Pooransingh; J Tempowski; S Palmer; T Meredith (The World Health Organization, 2005)
OBJECTIVE: In December 2001, an expert consultation convened by WHO identified strengthening national and global chemical incident preparedness and response as a priority. WHO is working towards this objective by developing a surveillance and response system for chemical incidents. This report describes the frequency, nature and geographical location of acute chemical incidents of potential international concern from August 2002 to December 2003. METHODS: Acute chemical incidents were actively identified through several informal (e.g. Internet-based resources) and formal (e.g. various networks of organizations) sources and assessed against criteria for public health emergencies of international concern using the then proposed revised International Health Regulations (IHR). WHO regional and country offices were contacted to obtain additional information regarding identified incidents. FINDINGS: Altogether, 35 chemical incidents from 26 countries met one or more of the IHR criteria. The WHO European Region accounted for 43% (15/35) of reports. The WHO Regions for Africa, Eastern Mediterranean and Western Pacific each accounted for 14% (5/35); South-East Asia and the Americas accounted for 9% (3/35) and 6% (2/35), respectively. Twenty-three (66%) events were identified within 24 hours of their occurrence. CONCLUSION: To our knowledge this is the first global surveillance system for chemical incidents of potential international concern. Limitations such as geographical and language bias associated with the current system are being addressed. Nevertheless, the system has shown that it can provide early detection of important events, as well as information on the magnitude and geographical distribution of such incidents. It can therefore contribute to improving global public health preparedness.